1999
DOI: 10.1080/15216549900202023
|View full text |Cite
|
Sign up to set email alerts
|

Total reactive antioxidant potential in human saliva of smokers and non‐smokers

Abstract: Uric acid is the most important non-enzymatic antioxidant present in human saliva. There is a great variability among individuals, both in salivary uric acid content and saliva total reactive antioxidant potential (TRAP). The uric acid present in saliva correlates with plasma uric acid, suggesting that the former is imported from plasma. There are not statistical differences between uric acid or TRAP values in saliva of smokers and nonsmokers. Also, smoking a cigarette does not modify the levels of antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 1 publication
(1 reference statement)
1
26
1
5
Order By: Relevance
“…The latter is supported by our findings indicating a significantly reduced antioxidant defence of young smokers' lymphocytes estimated by the H 2 O 2 ‐induced DNA damage (comet assay), which may indicate a reduced intracellular antioxidant status, in comparison to non‐smokers. It must be noted here that the same method, but without the addition of H 2 O 2 ‐generating system, has been used before in order to detect differences between smokers and non‐smokers, with contradicting results (19,20). Plappert et al (21) did not detect any significant differences between smokers and non‐smokers in contrast to Betti et al (22) who observed significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is supported by our findings indicating a significantly reduced antioxidant defence of young smokers' lymphocytes estimated by the H 2 O 2 ‐induced DNA damage (comet assay), which may indicate a reduced intracellular antioxidant status, in comparison to non‐smokers. It must be noted here that the same method, but without the addition of H 2 O 2 ‐generating system, has been used before in order to detect differences between smokers and non‐smokers, with contradicting results (19,20). Plappert et al (21) did not detect any significant differences between smokers and non‐smokers in contrast to Betti et al (22) who observed significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated by various analyzed parameters, including the uric acid molecule (which is considered responsible for no less than 70% of the salivary antioxidant potential (25)(26)(27) and the two general salivary antioxidant analyses performed-TAS and ImAnOx. Concurrently we report, for the first time, that salivary MMPs are reduced in JIA and more so following anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke contains free radicals, which can damage tissues [1, 2]. Saliva plays a role in the general defense system of the oral environment, and in addition to antioxidants, it contains immunoglobulins, antibacterial enzymes, and growth factors.…”
Section: Introductionmentioning
confidence: 99%